A Teaching Mode for Art Anatomy Based on Digital Virtual Technology - Wang, Na (International Journal of Emerging Technologies in Learning (iJET), 2018)
Art anatomy is a morphological science characterized with the use of many terms and descriptions that are difficult to remember. The traditional art anatomy teaching mode pays attention to explanation of theoretical knowledge in the classroom using simple teaching methods, so that the teaching is boring. Consequently, students have low interest in learning, which affects the quality of teaching. With this regard, an Art Anatomy teaching mode was proposed in this study based on digital virtual technology. It uses digital virtual technology to build 3D models and database of art anatomy teaching specimens. Due to the powerful modeling functions and production effect of 3DS MAX, MAYA software and VRML to render realistic scenes, the preservation and recording of the initial state of the anatomical specimens can save various types of data and spatial relationships of the specimens to the greatest extent. Based on the teaching practice in the course of “Art Anatomy” at Liaoning University of Science and Technology in Liaoning Province, China, the teaching mode proposed in this paper was found to be highly efficient, concrete and easy to understand, and students had a high degree of recognition for this teaching method. A new idea and method were thereby provided for the teaching reform of art anatomy.